2014
DOI: 10.1155/2014/140618
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Stem Cell Therapy for Erectile Dysfunction

Abstract: Stem cell (SC) therapy for erectile dysfunction (ED) has been investigated in 35 published studies, with one being a small-scale clinical trial. Out of these 35 studies, 19 are concerned with cavernous nerve (CN) injury-associated ED while 10 with diabetes mellitus-(DM-) associated ED. Adipose-derived SCs (ADSCs) were employed in 18 studies while bone marrow SCs (BMSCs) in 9. Transplantation of SCs was done mostly by intracavernous (IC) injection, as seen in 25 studies. Allogeneic and xenogeneic transplantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 176 publications
(260 reference statements)
0
8
0
Order By: Relevance
“…[16,57,58] Recently, the reconstruction of muscles based on regenerative medicine using a variety of biomaterials, cells, and bioactive molecules has been intensively attempted by many researchers, and somewhat promising results have been demonstrated. [7][8][9][10][11][12][13][14][15][16][17][18] However, the reinnervation of regenerated muscles has not yet been profoundly considered, even though reinnervation is an essential requirement to maintain muscle functions. Therefore, the aim of this study was the preparation of a bioactive molecule-loaded matrix system which can induce effective neurogenic differentiation of progenitor cells/ stem cells around the muscles and thus allow a reinnervation of the muscles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16,57,58] Recently, the reconstruction of muscles based on regenerative medicine using a variety of biomaterials, cells, and bioactive molecules has been intensively attempted by many researchers, and somewhat promising results have been demonstrated. [7][8][9][10][11][12][13][14][15][16][17][18] However, the reinnervation of regenerated muscles has not yet been profoundly considered, even though reinnervation is an essential requirement to maintain muscle functions. Therefore, the aim of this study was the preparation of a bioactive molecule-loaded matrix system which can induce effective neurogenic differentiation of progenitor cells/ stem cells around the muscles and thus allow a reinnervation of the muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a variety of attempts based on regenerative medicine have been conducted for this purpose. Several investigators have reported that various progenitor cells or stem cells [7][8][9][10][11][12][13][14][15] and continuously released bioactive molecules [16][17][18] can enhance the regeneration of muscles and thus help to treat chronic degenerative diseases. However, the regeneration of muscles alone cannot be a fundamental cure of chronic degenerative diseases, because regenerated muscles with insufficient nerve connections subsequently lead to muscle atrophy.…”
Section: Introductionmentioning
confidence: 99%
“…ADSCs are a distinct population of MSCs, which reside in the perivascular niche of the adipose tissue [ 54 ]. The broad use of these cells could be attributed to their easy isolation by specific devices, their abundance in the tissues, their similar properties to BMSC and their proven therapeutic efficacy [ 15 ]. The isolation of such cells demands firstly the separation of the SVF from the adipose tissue harvested, as already mentioned.…”
Section: Clinical Studies: Type Of Stem Cells Preparation and Effmentioning
confidence: 99%
“…Unfortunately, the treatment failure levels with PDE5is are unacceptably high. Among patients using PDE5is, approximately 20% of those who had ED without other comorbidities and 40% of those with diabetes mellitus or underwent a prostatectomy remained unresponsive to these treatment procedures [ 15 ]. Therefore, additional treatment options for the management of ED are needed and include the use of intracorporal injections, vacuum erection devices and penile prosthesis implantation.…”
Section: Introductionmentioning
confidence: 99%
“…These regenerative effects could be ascribed to the anti-apoptotic activity and paracrine effect of iPSCs' secretome. Besides, other sources of stem cells such as umbilical cord, skeletal muscles, penile tissues, and skin have been explored to develop regenerative treatment for ED [73]. Neural embryonic stem cells (NES) have also been administered in corpus cavernosal tissues and MPG to regenerate cavernosal nerve from crush injury [74].…”
Section: Induced Pluripotent and Other Stem Cell-based Approaches For Edmentioning
confidence: 99%